The structure of cytochrome c′3 from desulfovibrio gigas (NCIB 9332) - R P Ambler (1969)
The species of the genus Desulfovibrio [ 1,2] differ markedly in their morphology and in their DNA base ratio [3,4], but have a generally similar metabolism, and all possess two diagnostic pigments, desulphoviridin and cytochrome ~3.In this paper the amino acid sequences of cytochrome c3 from two species of Desulfovibrio are compared.In 1958 Postgate [5] isolated cytochrome c3 from the organism now known as D. vulgaris (NCIB 8303; strain Hildenborough), and showed it to be similar to mammalian cytochrome c in molecular weight and absorption spectrum, but to have a remarkably low oxidation-reduction potential (-205 mV) and at least two haem groups per molecule.The amino acid sequence has been determined [6] and shows no similarity to that of other c-type cytochromes.In 1963 Le Gall [7] isolated a new species, D. gigas (NCIB 9332), and from it cytochrome c; has been isolated [8].This protein is similar to the original cytochrome c3 in molecular weight and oxidationreduction potential, but has a very different isoelectric point (pH 5.2 rather than lO.S), major differences in amino acid composition, and different terminal groups [9].We have now examined the amino acid sequence of the protein (fig.l), and are able to show that the sequence is so similar to that of cytochrome c3 that the proteins must be considered homologous.Cytochrome c$ was prepared as previously described [8] .The haem was removed by reduction North-Holland